Biosorption Of Copper Using Immobilised Eucheuma Cottonii Sp.Biomass By Using Response Surface Methodology (RSM) - Nur Mashitah, Mohd Nawi (2023)
Heavy metal, sometimes known as toxic metal, is a form of industrial effluent that is often produced by chemical waste, manufacturing, sewage, electroplating, and mining. Biosorption is a low-cost method for heavy metal removal in wastewater. The purpose of this study is to assess the effectiveness of immobilised seaweed as a copper removal biosorbent in terms of initial contact time, dosage and initial concentration and to optimise the performance of immobilised seaweed by using Response Surface Methodology-Central Composite Design (RSM-CCD) for carried out biosorption process. To make the aqueous solution of copper, 150ml of CU(NO3)2 was dissolved in 850ml of distilled water to get 1000 mg/L of Cu2+ solution. A total 20 runs were carried out to generate a quadratic model in RSM-CCD. The requisite quantities of Cu2+ solution was generated by diluting the stock solution with suitable dilutions. The initial Cu content in synthetic wastewater is determined. The spectrophotometer was used to determine the final concentration of heavy metal in the sample. The seaweed will be immobilised and washed with distilled water. The activating reagent, 3g of sodium alginate solution, was produced in a 1000ml beaker that had been cleaned and dried. 0.25g seaweed powder is added to the solution while it is still being stirred. Then combine and set aside to cool to room temperature. Using a syringe, the mixture was then injected into a 3g calcium chloride solution. Finally, wait at least an hour before using the solution. Following that, the treated alginate beads were converted into CaCl2 and washed with distilled water. The dried beads of immobilised seaweeds are exposed to air for half an hour after being dried with filtered paper. Immobilized Eucheuma Cottonii sp., known as red seaweed, has been employed as a biosorbent to extract heavy metals from industrial effluent. The final concentration of heavy metal was determined using spectrophotometer. After optimization, model State-Ease Design Expert version 7.0 by Ching Liu RSM-Central Composite Design (CCD) was used for biosorption process experimental. 20 runs created a linear model. Finally, ANOVA model verification showed that the ANOVA model (R²=0.5414, adj-R²= 0.4554) can accurately predict. In conclusion, immobilised Eucheuma Cottonii might be a natural biosorbent for copper ion removal.